Absolute Bioavailability, Mass Balance, and Metabolic Profiling Assessment of [14C]‐Belumosudil in Healthy Men: A Phase 1, Open‐Label, 2‐Part Study - Schueller, Olivier; Skucas, Ed; Regev, Galit; Shaw, Iain; Singh, Nand; Sanghvi, Mitesh; Croft, Marie; Lohmer, Lauren; Alabanza, Anginelle; Patel, Jeegar (Clinical pharmacology in drug development, 2022)
Belumosudil is a selective Rho‐associated coiled‐coil containing protein kinase 2 (ROCK2) inhibitor. ROCK2 has been shown to drive proinflammatory response and fibrosis that occurs with chronic graft‐versus‐host disease; therefore, inhibition of ROCK2 has emerged as a therapeutic target for chronic graft‐versus‐host disease. In this phase 1 two‐part study, the pharmacokinetics, mass balance, and metabolic profile of belumosudil were evaluated after single doses of unlabeled belumosudil oral tablets (200 mg), radiolabeled belumosudil intravenous (IV) microtracer infusions (100 μg), and radiolabeled oral capsules (200 mg). Absolute bioavailability based on area under the plasma concentration–time curve from time 0 to infinity for the oral dose/area under the plasma concentration–time curve from time 0 to infinity for the IV dose was calculated as 63.7%. Radiolabeled IV microtracer dosing demonstrated a low extraction ratio and distribution of belumosudil into tissues. The majority of total radioactivity was recovered in feces, with minimal amounts recovered in urine, suggesting minimal renal elimination of belumosudil. In addition to parent and main metabolite KD025m2, metabolites identified in plasma included the phase 2 metabolites O‐dealkylated belumosudil sulfate and belumosudil glucuronide. These metabolites (with the exception of the glucuronide) in addition to monohydroxy‐belumosudil, and belumosudil diol were identified in feces. No metabolites in urine accounted for >10% of the radioactive dose.